Case report: tumefactive demyelinating lesions after the second cycle of alemtuzumab in multiple sclerosis; immune cell profile and biomarkers - Rabaneda-Lombarte, Neus; Teniente-Serra, Aina; Massuet-Vilamajó, Anna; Ramo-Tello, Cristina; Presas-Rodríguez, Silvia (Frontiers in Immunology, 2024)
Objective: We present a case of multiple tumefactive demyelinating lesions (TDLs) emerging 24 months after the 2nd cycle.A woman with relapsing MS discontinued fingolimod due to gestational desire, experiencing severe disease exacerbation. Alemtuzumab was initiated with clinical, radiological and immunological monitoring.Results: Before the 2nd cycle, she relapsed with 12 T1Gd+ lesions and peripheral blood showed increased B-cells and decreased T-cells. At 24 months after the 2nd cycle, she developed cognitive impairment and the brain MRI showed multiple T1Gd+ lesions, including TDLs. We found again an increase of B-cells, but also of CD4 Th1 central memory. Th1/Th17 cells increased 3 months before LTDLs detection.Conclusions: TDLs can appear 24 months after the 2nd cycle of alemtuzumab in MS. Increased Th1/Th17 cells could be a candidate biomarker of TDLs in alemtuzumab-treated MS.